The Relationship Levels of Consumption and Physical Activity with Nutritional Status of Staff and Personnel Addendant General of Military Resort (AJENREM) Type B 081 Madiun - Dian Putri Agustina; Annas Buanasita; Inne Soesanti; Juliana Christyaningsih (Journal of Nutrition Explorations, 2023)
Nutritional status is closely related to health. Nutrition plays an important role in the body as a provider of energy, maintaining body tissues and regulating metabolic processes in the body, including for military personnel who are required to have optimal physical conditions. This study aims to determine the relationship between the level of consumption and physical activity with the nutritional status of the staff and personnel of AJENREM Type B 081 Madiun. This study used a cross-sectional design with a sample of 43 respondents, which was conducted using a simple random sampling technique. Data were collected by measuring weight, height, filling out the IPAQ-Short questionnaire and interviewing food recall 2x24 hours. Relationship analysis was carried out using the Spearman Rho test. The results showed that there was no relationship between the level of energy consumption, protein, fat and carbohydrates with nutritional status. There was a significant relationship between physical activity (p=0.000) and the nutritional status of the staff and personnel of AJENREM Type B 081 Madiun. Therefore, more physical activity is recommended in maintain the optimal nutritional status.